2013
DOI: 10.1097/aln.0b013e318277a81c
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Hypersensitivity after Nerve Injury from Systemic Donepezil Involves Spinal Cholinergic and γ-Aminobutyric Acid Mechanisms

Abstract: Background: Evoking spinal release of acetylcholine (ACh) produces antinociception in normal animals and reduces hypersensitivity after nerve injury, and some studies suggest that ACh-mediated analgesia relies on γ-aminobutyric acid (GABA)-ergic signaling in the spinal cord. In this study, the authors tested the spinal mechanisms underlying the antihypersensitivity effects of donepezil, a central nervous system-penetrating cholinesterase inhibitor, in a rat model of neuropathic pain. Methods: Male Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…This study showed that donepezil inhibits ICS-induced fibromyalgia-like pain via supraspinal mechanisms, whereas it blocks neuropathic pain via spinal mechanisms (Kimura et al, 2013). Such different pharmacotherapeutical actions against neuropathic pain and ICS-induced fibromyalgia-like pain can be observed in gabapentinoid actions, as described above.…”
Section: Discussionmentioning
confidence: 73%
“…This study showed that donepezil inhibits ICS-induced fibromyalgia-like pain via supraspinal mechanisms, whereas it blocks neuropathic pain via spinal mechanisms (Kimura et al, 2013). Such different pharmacotherapeutical actions against neuropathic pain and ICS-induced fibromyalgia-like pain can be observed in gabapentinoid actions, as described above.…”
Section: Discussionmentioning
confidence: 73%
“…In a rat model of spinal nerve ligation (SNL), donepezil administration results in an attenuation of mechanical hyperalgesia through a spinal muscarinic mechanism (Clayton et al, 2007). This analgesic effect could also involve spinal nicotinic and GABAergic receptors, but it is still unclear whether this effect of donepezil is directly due to an increase of spinal Ach release (Kimura et al, 2013). Indeed, cholinergic analgesia is only observed in neuropathic pain conditions, but the peak level and the time course of the Ach increase after donepezil treatment using spinal microdialysis were similar between normal and SNL rats (Kimura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This analgesic effect could also involve spinal nicotinic and GABAergic receptors, but it is still unclear whether this effect of donepezil is directly due to an increase of spinal Ach release (Kimura et al, 2013). Indeed, cholinergic analgesia is only observed in neuropathic pain conditions, but the peak level and the time course of the Ach increase after donepezil treatment using spinal microdialysis were similar between normal and SNL rats (Kimura et al, 2013). Furthermore, the spinal basal levels of ACh were not significantly different between normal and SNL rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations